Growth Strategy for Small Businesses: The case of OfficePro Direct - Sharma, Dhritiman (2016)
This report discusses the growth strategy for small businesses with an example of OfficePro Direct, an office supplies and stationery products distributor in Nottingham. The report unfolds to discover the approach taken to derive the growth strategy by exploring the organisation's internal core functions and external variables; like competitive positioning, economic surroundings, market conditions etc. It uses various relevant management frameworks, primary academic and industry research to formulate a short and long term growth strategy plan for OfficePro Direct's marketing and operation functions. It also discusses best practices for small businesses to implement the strategy suggested.